You could have added -2x to each side and the x-values would be on the right in the form 6 = -2 + 2x. It's just more natural to have x on the left. But if you do it the other way, you can just switch each side of the equation and say -2 + 2x = 6. It doesn't matter which way you do it so long as you manage to get all of the x's on one side.
2006-11-17 07:43:19
·
answer #1
·
answered by Clueless 4
·
0⤊
0⤋
im going to tell u that,there are 2 things in this world that u can do everything u like with them :
1 - your life
and 2 - an equation!
in an equation,the main goal is to find "what we are looking for",so,i prefer to solve this equation like this:
6 + 2x = -2 + 4x
(add a 4): 10 + 2x = 2 + 4x
(multiply by 5) : 50 + 10x = 10 + 20x
(divide by 10) : 5 + x = 1 + 2x
(minus an x) : 5 = 1 + x
(and if u are satisfied enough,minus a 1) : 4 = x
see,there's nothing to worry about.
so, a life and an equation is similar,but the difference is, in life,we dont exactly know "what we are looking for"!.
hope it helps
2006-11-17 08:50:42
·
answer #2
·
answered by farbod f 2
·
0⤊
0⤋
Struggling with algebra?
ok heres the example
Solving
6 + 2x = -2 + 4x subtract 4x from each side
6-2x=-2 subtract 6 from each side
-2x=-4 divide by -2
x=2
2006-11-17 07:55:18
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
I think you mean "add -2x". In fact, that approach is equally valid, except the "x" terms end up on the right side of the equation. It is conventional to get the unknown term (x) on the left side, but not really necessary. Add -2x to both sides to get 6 = -2 + 2x; then add 2 to both sides to get 8 = 2x. The other way, add -4x to both sides to get 6 - 2x = -2, then add -6 to both sides to get -2x = -8; multiply by -1 to get 2x = 8. Same result, just that the "x" term is on the other side.
2006-11-17 07:44:16
·
answer #4
·
answered by gp4rts 7
·
0⤊
0⤋
you will use the identity property for addition and multiplication, +a -a = 0 or a/a =1 and whenever you add, subtract,multiply,divide,square,or take the square root of one side of an equation you need to do the same to the other side.
the steps to your solution for your equation could go like this
6+2x = -2+4x, 6+2x-2x=-2+4x-2x, 6=-2-2x,6+2=2-2-2x,8=-2x,8/-2=-2/-2x,-4=x
2006-11-17 07:44:36
·
answer #5
·
answered by gggjoob 5
·
0⤊
0⤋
6 + 2x = -2 + 4x
8 + 2x = 4x (added -2 to the left side of the equation)
8 = 2x (added -2x to both sides of the equation)
x = 4 (divided by 2)
2006-11-17 07:40:59
·
answer #6
·
answered by Peter 2
·
0⤊
0⤋
It's Ok! Because -4x will do away by itself if you will put it to another side. Foe ex:
6 + 2x + -4x = -2 + 4x + -4x
6 + 2x = -2 + 4x + (-4x +4x)
It is very good way when you are solving big problems, just learn how to use that!
6 + 2x + -4x = -2 + 4x + -4x
6-2x=-2
x=4
2006-11-17 07:39:36
·
answer #7
·
answered by Vladimir S 2
·
0⤊
0⤋
moving '4X' or '2X' the result will come out the same.
you dont need to worry about it. As long as you remember to put a minus sign in the front.
i.e (4x)
6 + 2X = -2 + 4X
6 + 2X -(+4X)= -2 + 4x -(4X)
6 - 2X = - 2
6 - (6) - 2x = -2 - 6
-2x = -8 (take the minus sign away)
2x = 8
x =4
i.e. (2x)
6 + 2X = -2 + 4X
6 + 2X - (2X) = -2 +4X - (2X)
6 = -2 + 2X
6 - (-2) = -2 + 2X - (2)
8 =2X
4 = X
Both answer are the same!
2006-11-17 07:49:20
·
answer #8
·
answered by ? 2
·
0⤊
0⤋
here's how i'll solve it ..
6 + 2x = -2 + 4x
transpose ..
2x - 4x = -2 -6
-2x = -8
divide both sides by -2
x = 4 ..
let me try yours ..
6 + 2x + -4x = -2 + 4x + -4x
6 - 2x = -2
transpose ..
-2x = -2 -6
-2x = -8
divide both sides by -2
you'll still get
x =4 ..
mine is really easier ..
2006-11-17 16:05:16
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
You have 4x on the right. Adding -4x to everything is your way of removing it from the right-hand side.
Continuing your process...
6 + 2x + -4x = -2
The 4x and -4x on the right added up to zero and canceled each other!
2006-11-17 07:44:29
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋